2022
DOI: 10.3389/fimmu.2022.847132
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals the Systematic Relationship Between Oral Homeostasis and Chronic Sleep Deprivation in Rats

Abstract: Sleep disorders were associated with oral health. Inflammation has especially been thought to be a key factor in linking oral diseases and sleep deficiency. However, how chronic sleep deprivation (CSD) affects oral homeostasis, particularly oral inflammation and oral microbiota, is still unknown. This study aimed to uncover the systematic relationship between oral homeostasis and CSD in rats. The metabolomics in serum, proteomics in the tongue tissues, and microbiome analysis in the oral cavity in CSD rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Our results regarding the impaired mitochondrial electron transport chain are consistent with those of previous studies on both SD and MCI ( Morris et al, 2021 ; Chen et al, 2022 ), thus indicating that deficiencies in energy-generating mitochondrial pathways play an important role in cognitive impairment induced by SD. In addition, among the 32 MitoDEGs involved in metabolism, 11 genes are implicated, including six in lipid metabolism (ACADL, THEM4, ACSM3, LYPLA1, TSPO, and SCP2), one in carbohydrate metabolism (HMGCL), one in amino acid metabolism (GLS2), and one in nucleotide metabolism (FHIT), ( Figure 8B ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results regarding the impaired mitochondrial electron transport chain are consistent with those of previous studies on both SD and MCI ( Morris et al, 2021 ; Chen et al, 2022 ), thus indicating that deficiencies in energy-generating mitochondrial pathways play an important role in cognitive impairment induced by SD. In addition, among the 32 MitoDEGs involved in metabolism, 11 genes are implicated, including six in lipid metabolism (ACADL, THEM4, ACSM3, LYPLA1, TSPO, and SCP2), one in carbohydrate metabolism (HMGCL), one in amino acid metabolism (GLS2), and one in nucleotide metabolism (FHIT), ( Figure 8B ).…”
Section: Discussionsupporting
confidence: 92%
“…Chronic sleep deprivation induces oral and systemic inflammation in rats 20 . Therefore, we assessed IL-6 and IL-1β mRNA expression in control and CSD tongue tissues and antigen levels in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Salivary concentrations of amyloid-β 14 , 18 and tau 19 reflect cognitive dysfunction. Proteomic profiling has revealed that neurodegenerative and inflammatory pathways are enriched in tongue tissues from rats with chronic sleep deprivation 20 . However, the effects of CSD on salivary metabolic profiles remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sleep has been linked to alterations in oral microbiome. Recently, chronic sleep deprivation was shown to alter oral microbiome, and cause oral and systemic inflammation in rats [ 16 ]. These findings suggested that healthy lifestyles, like regular exercise and sufficient sleep, are beneficial to oral and cardiovascular health.…”
Section: Therapeutic Insights On Oral Dysbiosis In Cvdsmentioning
confidence: 99%